MODES OF THINKING IN LANGUAGE STUDY - Jesus Martinez del Castillo (European Scientific Journal, ESJ, 2014)
The concept of language is nothing but a linguistic simplification. It encompasses many realities. Depending on the language spoken, the reality of language is denoted with words belonging to different grammatical categories. The reality implicit in these grammatical categories involves a particular mode of thinking, prompted by the conception of things in accordance with a corresponding mode of being. Because of this it is necessary, then, to distinguish the concept of language as something different from the reality of language and determine the reality or degree of reality of it.